Thermochronology data (AFTA) from the easternmost Eastern Alps - Bianca Heberer; Bernhard Salcher; Gabor Tari; Godfrid Wessely; István Dunkl; Reinhard F Sachsenhofer; Michael Wagreich; Christoph von Hagke (PANGAEA, 2024)
We carried out apatite fission track and apatite (U-Th)/He dating on Flysch, Lunz and Gosau sandstones from the easternmost Eastern Alps. Late Oligocene to Miocene cooling ages capture a hitherto un(der)appreciated pulse of exhumation. This pulse is related to the Bohemian Spur of the downgoing European plate.